Vital pulp therapy: an alternative to root maturation of a tooth with superficial micro abscess (Research, Society and Development, 2020)
Maintenance of pulp functional integrity should be aimed by the treatment of trauma affected immature permanent teeth. The prognosis of vital pulp therapies (VPT), when well indicated and correctly performed, not only preserves pulp vitality but also provides the immature root development. This case reports the treatment of a patient with a crown fractured immature maxillary right central incisor. Clinical examination, radiographic inspection and sensitivity tests confirmed tooth vitality. In spite of the superficial micro abscess presence, pulpotomy was the treatment of choice according to the pulp vitality characteristics found during the undergoing surgery. Root development and apical closure were verified at the 1st year radiographic control. After 3 years of follow-up, even with the occurrence of 3 new traumatisms, the treated tooth showed radiographic sound characteristics. Nevertheless, on the fourth-year return, the conventional endodontic treatment had to be carried out due to radiographic signal of initial root obliteration. It was concluded that pulp vitality diagnosis step and clinical-radiographic follow-up are extremely important for the pulpotomy outcome.  This conservative approach resulted in success since it induced root development and apical closure, permitting the posterior execution of the endodontic therapy.